Effects of tungsten on vacancy aggregation behavior and its induction for interstitial and vacancy migration in tantalum–tungsten alloys: A first-principles study. (April 2023) - Tian, Huaigu; Zhu, Hongjuan; Zheng, Yanfei; Mao, Shuangsuo; Zhou, Xiaohua; Cao, Zelin; Pan, Min; Wen, Shulong; Li, Rusong
Highlights: Vacancy will cause W to cluster around the vacancy and form an octahedral structure. W induces the migration of vacancy and interstitial, evolving the self-interstitial of Ta into the Ta-W interstitial. Tungsten has an inhibitory effect on the formation of vacancy clusters, and this inhibition increases with rising tungsten atoms. Abstract: Tantalum–tungsten (Ta–W) alloys have been considered candidates for plasma-facing materials (PFMs) in advanced nuclear fusion design due to their excellent thermal and mechanical properties. Herein, the effects of tungsten (W) on the clustering and migration of vacancies and interstitials in Ta are studied using first-principles calculations. We find that W can attract vacancies at the second nearest neighbor position, causing the original non-clustered W to gather around the vacancies, forming an octahedral cluster structure. However, as the number of W atoms increases, W exerts a progressive inhibitory effect on the formation of vacancy clusters. Furthermore, this work confirms that W induces the migration of vacancies, thus significantly improving the mobility and recombination ability of vacancies. Similarly, W also induces the migration of interstitial atoms in addition to reducing the interstitial rotation threshold energy, leading to an evolution of Ta–Ta interstitial to Ta–W interstitial. Therefore, it can be speculated that W not only plays a vital positive role in the combination between interstitials and vacancies, but also can effectively inhibit the formation of voids by adding W, and then improving the anti-irradiation ability of Ta–W alloy material under neutron irradiation.